Optimization Strategy of Laku Pandai Policy in Islamic Bank: A Case Study - Junarti Bakhtiar; Saiful Anwar; Fitra Anisa (Tazkia Islamic Finance and Business Review, 2017)
Laku Pandai is a program providing banking services and/or other financial services through cooperating with other parties (bank agents) and supported by the usage of modern facilities to increase and expand any accesses to financial services. Laku Pandai is quite effective and efficient if its implementation and optimization are conducted by the banks that are eager in expanding their services in lower average cost. As for how it is, its significant development then triggered BRI Sharia to participate. However, Financial Services Authority thinks that conventional banking is not yet optimal, so it comes up with an argumentative assumption on sharia banking if it successfully implements the program. The purpose of this study is to determine appropriate strategies for optimizing Laku Pandai outputs in sharia banking using SWOT and AHP analysis. SWOT analysis is used to determine internal and external factors related to application of the output, while AHP is used to capture the best precise strategy. The result of the research shows that the main output of Laku Pandai is to successfully reach unbanked people with the exact alternative that is by improving marketing and promotion, improving socialization and education to society, improving agent quality and establishing vision and mission.